Avaliação das propriedades do ligante asfáltico modificado com borracha de pneus tratada por processo termomecânico - Fernandes, Paulo Victor de Araújo (2023)
Tire recycling poses a challenge due to its non-biodegradable nature and the increasing volume of waste. The asphalt paving industry plays a crucial role by incorporating ground tire rubber (GTR) into modified asphalt binder production, bringing benefits in terms of road maintenance, lifespan, and environmental impact reduction. However, rubberized asphalt faces challenges like phase separation and high viscosity. Solid-State Shear Extrusion (SSSE) technology emerges as a promising alternative to enhance compatibility and adhesion between rubber and asphalt. This study aimed to investigate the properties of modified asphalt binder CAP 50/70 with rubber treated by SSSE. Ground tire rubber (GTR) was produced, both pulverized and partially devulcanized, at two temperatures (100 and 200°C), identified as dGTR100 and dGTR200. Asphalt-rubber samples (LGTR, LdGTR100, and LdGTR200) were prepared with rubber contents of 15, 20, and 25 % by weight of the binder. Physical-chemical, morphological, and thermal tests showed modifications in rubber characteristics post-SSSE, highlighting the temperature's influence on final material properties. Rheological tests indicated superior performance of asphalt-rubber over pure binder, with rubber content and characteristics significantly impacting binder properties. LdGTR100 exhibited better performance than LGTR at high temperatures and storage stability at 20 % rubber content. Therefore, the treatment of rubber by SSSE optimized the interaction between rubber and binder, improving the rheological properties of the rubber asphalt and highlighting its significant potential in the production of modified asphalt binders.